Safety and PK/PD correlation of TV-1106, a recombinant fused human albumin-growth hormone, following repeat dose administration to monkeys. (October 2016) - Ashkenazi, Nurit; Rosenstock, Moti; Hallak, Hussein; Bassan, Merav; Rasamoelisolo, Michele; Leuschner, Jost; Shinar, Doron
Abstract: Purpose: TV-1106 is a recombinant human albumin genetically fused to growth hormone which is intended to reduce the frequency of injections for GH therapy users. We report the safety, tolerability, pharmacokinetics and pharmacodynamics of repeated subcutaneous injections of TV-1106 in Cynomolgus monkeys. Method: Cynomolgus monkeys received four weekly subcutaneous injections of 0, 5, 10 or 20 mg/kg TV-1106 and were monitored for safety signals throughout the study. Serum levels of TV-1106 and insulin-like growth factor 1 (IGF-1) were assayed. Results: Treated animals showed no adverse effects or histopathological changes. TV-1106 serum concentrations showed sustained exposure to the drug. Exposure increased in a dose-dependent manner with peak concentrations at approximately 24 h post-dosing and elimination half-lives in the range of 12 to 24 h. IGF-1 serum concentrations were elevated throughout the entire study duration, indicative of the pharmacological response. There was a clear correlation between change in IGF-1 levels and dose or exposure to TV-1106. Conclusions: The safety, pharmacokinetic and pharmacodynamic findings support the further development of TV-1106 as a once-weekly administered treatment for patients with GHD. Highlights: TV-1106 is a long acting recombinant GH which was tested pre-clinically. Treated animals showed no adverse effects and IGF-1 serum levels were elevated. There was a clear correlation between change in IGF-1 levels and TV-1106 exposure. TV-1106 was shown to be safe, long acting and pharmacodynamically active.